Solar Cells: Low‐Temperature Plasma Processing of Platinum Porphyrins for the Development of Metal Nanostructured Layers (Adv. Mater. Interfaces 14/2017). Issue 14 (21st July 2017) - Filippin, Alejandro Nicolas; Sanchez‐Valencia, Juan Ramon; Idígoras, Jesús; Macias‐Montero, Manuel; Alcaire, Maria; Aparicio, Francisco Javier; Espinos, Juan Pedro; Lopez‐Santos, Carmen; Frutos, Fabian; Barranco, Angel; Anta, Juan Antonio; Borras, Ana
Abstract : Platinum layers show a superior catalytic performance as counterelectrodes in dye‐sensitized solar cells. Combined vacuum and plasma processing of Pt‐porphyrin opens a versatile route for the development of nanostructured platinum including two‐dimensional extended percolated layers and one‐dimensional porous nanocolumnar films. This is demonstrated by Juan Ramon Sanchez‐Valencia, Ana Borras, and co‐workers in article number1601233 .